Penguatan Potensi Desa Wisata Berbasis Partisipasi Masyarakat Lokal di Desa Legokjawa Kecamatan Cimerak Kabupaten Pangandaran - Iwan Satibi; Yaya Mulyana; Kamal Alamsyah; Lia Muliawaty (JURNAL ABDIMAS SERAWAI, 2022)
The development of tourism potential is a necessity that cannot be ignored, following the determination of Pangandaran Regency as a Special Economic Zone (SEZ) and a world-class tourist destination. One of the efforts that can be made to realize these expectations is to strengthen the potential of tourist villages that emphasize the participation of local communities. Legokjawa Village is one of the tourist villages that has considerable potential in supporting the development and improvement of tourism objects in Pangandaran Regency. However, the problem is that the various tourism potentials owned by Legokjawa Village appear to have not been fully managed optimally, especially those related to the involvement of local communities in supporting the development of these tourism objects. Given the importance of developing these tourism objects, it is necessary to strengthen the potential of tourism villages based on local community participation. Thus, the potential development of the tourism village can not only be enjoyed by tourists, but also can encourage and improve the welfare of the local community